GmBTB/POZ promotes the ubiquitination and degradation of LHP1 to regulate the response of soybean to Phytophthora sojae - Chuanzhong Zhang (Nature Portfolio, 2021)
Zhang et al characterise the mechanism by which GmBTB/POZ enhances resistance to P. sojae in soybean. They show that GmBTB/POZ directly associates with the heterochromatin protein GmLHP1 and mediates its degradation to regulate the salicylic acid signaling pathway, providing insights into the defence against a common soybean disease.